Growth and physiological responses of oil palm seedlings to two sources of potassium - Hamzah, Marzita (2012)
A study was conducted to determine the effects of different sources of potassium on the physiological characteristics of oil palm seedlings. Three month old oil palm seedlings of Deli Yangambi and Deli Avros were raised in polybags filled with Serdang series soils. The treatments were applied one month after stabilizing the crop. The treatments comprised of two sources of potassium, potassium chloride (MOP) and potassium sulfate (SOP), applied at four different rates (0, 50, 100 or 150 g K2O/seedling). The three factor experiment comprising of two progenies, and two K sources at four levels each, was carried out in a glasshouse and arranged in a randomized complete block design with three replications. The objectives of this experiment were to determine the effect of different sources and rates of potassium on the growth and physiological responses of young oil palm seedlings and to determine interactions between palm progenies and potassium sources and rates. Preliminary analysis prior to application of treatments included soil analysis, fertilizer analysis, crop physiological analysis and nutrient analysis. Monthly physiological and growth measurements included net photosynthesis, stomatal conductance, relative chlorophyll content, transpiration rate, water use efficiency, plant height, leaf area, and total biomass. Growth parameters, physiological responses and nutrient status were significantly influenced by the interaction of progenies, potassium sources and rates. RGR increased 18% when treated with SOP compared to MOP at the rate of 100 g K2O/seedling. Net photosynthesis was 17% higher in Deli Yangambi and 6% higher in Deli Avros when treated with MOP at the rate of 100 g K2O/seedling. Results showed positive associations among the parameters. Stomatal densities at the abaxial surface had significant correlations with frond numbers (r = 0.5315), leaf area (r = 0.6822), basal diameter (r = 0.6399) and water use efficiency (0.5711). Stomatal conductance was positively correlated with water use efficiency (r = 0.5151) and transpiration rate (r = 0.5374). Positive relationships was observed between nutrients such as total nitrogen and total potassium (r = 0.8910). Nutrient uptake was affected by stomata conductance, as revealed by the positive association between total phosphorus (r = 0.6663) and total magnesium (r = 0.7842) with stomata conductance. In conclusion, SOP at the rate of 150 g K2O/seedling was the best source to increase vegetative growth of young oil palm seedlings. With respect to progeny Deli Avros was the more responsive progeny to the potassium treatments compared to Deli Yangambi.